Analisis Kepuasan Konsumen terhadap Kualitas Produk di Bebeke Om Aris Cabang Bogor - Ikhsanti Nuru Dinnisa; Syifa Az Zahra; Intan Nurmaharani; Salma Maulida Ahda; Ade Trisna Iswanda; Ahmad Rifqi; Khoirul Aziz Husyairi; Tina Nur Ainun (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
This study analyze consumer satisfaction with product quality at the 'Bebeke Om Aris' restaurant in Bogor. The analytical method used is Importance Performance Analysis (IPA) and Cartesian diagrams. Respondents used were 96 respondents with the convenience sampling method. The results showed that the highest consumer satisfaction was found in the display attribute of food presentation with a conformity level of 98.99%. The lowest consumer satisfaction is found in the texture attribute of the duck that is not tough with a suitability level of 80.67%. Quadrant A shows important attributes but not as expected by consumers which is the delicious aroma of food.